2021
DOI: 10.1021/acs.est.1c00901
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nanoscale Hydroxyapatite in Disease Suppression of Fusarium-Infected Tomato

Abstract: The present study investigated the mechanisms by which large-and small-sized nanoscale hydroxyapatite (nHA) suppressed Fusarium-induced wilt disease in tomato. Both nHA sizes at 9.3 mg/L (low) and 46.5 mg/L (high dose) phosphorus (P) were foliar-sprayed on Fusarium-infected tomato leaf surfaces three times. Diseased shoot mass was increased by 40% upon exposure to the low dose of large-sized nHA compared to disease controls. Exposure to both nHA sizes significantly elevated phenylalanine ammonialyase activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 76 publications
1
30
0
Order By: Relevance
“…This data supports the increased plant growth and development as reported in earlier sections on the application of nHAPs and nP. Although different from the present study, in another study with nHAPs, it had been shown that the application of nHAP ameliorates stress in Fusarium infested tomato plants . This supports our observation on inertness of nHAPs and nP on rice plants.…”
Section: Resultssupporting
confidence: 93%
“…This data supports the increased plant growth and development as reported in earlier sections on the application of nHAPs and nP. Although different from the present study, in another study with nHAPs, it had been shown that the application of nHAP ameliorates stress in Fusarium infested tomato plants . This supports our observation on inertness of nHAPs and nP on rice plants.…”
Section: Resultssupporting
confidence: 93%
“…Lycopersici in tomatoes, in a concentration- and size-dependent manner . In another study, Ma et al designed nanoscale hydroxyapatite (nHA) that suppressed the Fusarium-induced wilt disease in tomatoes . The study showed that the exposure of plants to nHA triggered the silicic acid-mediated defense phytohormone pathway, which then controlled the fungal infection .…”
Section: Resultsmentioning
confidence: 99%
“…Maximum crop production is known to be confounded by soil nutrient deficiencies . Globally, 30% of the cultivated soils are iron (Fe) deficient, where the plant available Fe content (not exceeding 10 –10 M) can be up to 4 orders of magnitude below that needed for optimal plant growth (10 –6 –10 –4 M). For example, Atencio et al (2021) reported that Fe deficiency induced 24% yield loss of soybean in the Upper Midwest, United States .…”
mentioning
confidence: 99%